BacScan: a novel genome-wide strategy for uncovering broadly immunogenic proteins in bacteria - Dong, Junhua; Zhang, Qian; Yang, Jinyue; Zhao, Yacan; Miao, Zhuangxia; Pei, Siyang; Qin, Huan; Jing, Changwei; Wen, Guoyuan; Zhang, Anding; Tao, Pan (Frontiers in Immunology, 2024)
In response to the global threat posed by bacterial pathogens, which are the second leading cause of death worldwide, vaccine development is challenged by the diversity of bacterial serotypes and the lack of immunoprotection across serotypes. To address this, we introduce BacScan, a novel genome-wide technology for the rapid discovery of conserved highly immunogenic proteins (HIPs) across serotypes. Using bacterial-specific serum, BacScan combines phage display, immunoprecipitation, and next-generation sequencing to comprehensively identify all the HIPs in a single assay, thereby paving the way for the development of universally protective vaccines. Our validation of this technique with Streptococcus suis, a major pathogenic threat, led to the identification of 19 HIPs, eight of which conferred 20-100% protection against S. suis challenge in animal models. Remarkably, HIP 8455 induced complete immunity, making it an exemplary vaccine target. BacScan's adaptability to any bacterial pathogen positions it as a revolutionary tool that can expedite the development of vaccines with broad efficacy, thus playing a critical role in curbing bacterial transmission and slowing the march of antimicrobial resistance.